A spin-wave frequency demultiplexer based on YIG nanowaveguides intersecting at a small angle - Nikolaev, Kirill O.; Raskhodchikov, D.; Bensmann, J.; Lomonte, E.; Jin, L.; Schmidt, R.; Kern, J.; Michaelis de Vasconcellos, S.; Bratschitsch, R.; Demokritov, S. O.; Pernice, Wolfram; Demidov, V. E. (Applied physics letters)
We experimentally demonstrate a simple design for a spin-wave frequency demultiplexer based on submicrometer-width yttrium iron garnet waveguides intersecting at an angle of 30°. We show that, depending on the frequency, spin waves excited in the input arm of the device are predominantly directed to one of the two output arms. This spin-wave routing is characterized by a large extinction ratio of about 10. The frequency response of the demultiplexer can be efficiently controlled by changing the static magnetic field and the geometry of the device. Due to the small intersection angle and symmetry of the device, its operation does not require conversion between different types of spin-wave modes. This results in a high efficiency of the device and allows its facile integration into magnonic networks for complex signal processing and computing with spin waves.
Gesehen am 11.11.2024